SISTEMA MOBILE MAPPING GEOSLAM ZEB HORIZON PER IL RILIEVO 3D DI UN POZZO - Simone Orlandini (mediaGEO soc. coop., 2021)
MicroGeo had the opportunity to experiment with the ZEB Horizon instrument to acquire a piezometric well in 3D. The scenario is not the easiest to detect. This type of wells, in fact, extends in depth for several tens of meters and with traditional scanning systems it is practically impossible to obtain a complete 3D acquisition of the subject. With the ZEB Horizon Mobile Mapping System it was possible to acquire the well. The subject presents itself as a 30 m deep piezometric well with a diameter of 3.6 m, with a high difficulty of acquisition: the extremely regular surfaces of the well have made the survey activity with the SLAM technique very complex, the algorithm that generates the 3D point cloud model must be extremely powerful in order to be able to generate a correct data even in a condition of extreme surface homogeneity.